Vem är de finska ordböckerna gjorda för? - Haarala, Risto (Nordiske Studier i Leksikografi, 1997)
So far, two comprehensive descriptive-normative dictionaries of the Finnish standard language have been compiled: "Nykysuomen sanakirja" (Dictionary of Modem Finnish) in 1951--61 and "Suomen kielen perussanakirja" (Basic Dictionary of the Finnish Language), printed form 1990-94 and CD-ROM version in 1997. I have tried to study to what extent future users were taken into account when the dictionaries were planned. For "Nykysuomen sanakirja" there is a fairly good amount ofwritten material which describes the background for the decisions made by the compilers. There is not much that would point to the idea of planning the contents and the structure of the entries with the users' point of view in mind. Some features of the dictionary al so indicate it. For instance, grammatical terms are abundantly used, and entries are more often structured on grammatical basis rather than according to semantic criteria. There are also documents ofthe planning phase of the "Suomen kielen perussanakirja". According to them, the goal was to compile an everyman's dictionary easy to use. However, the· solutions made have never been tested with any "ordinary" users. When new editions of"Perussanakirja" are planned, there would be a reason for doing a sufficient amount of user research. In the electronic form of the dictionary there will be good possibilities of describing language phenomena in different ways for different user groups.